(Mis)gendering and naming practices in appellate decisions in Santa Catarina’s state court - Rieger, Pedro; Figueiredo, Debora (Language and Law / Linguagem e Direito, 2017)
This study investigates practices of misgendering in appellate decisions involving claims for gender identity rights at the Tribunal de Justiça de Santa Catarina (TJSC). To do so, it relies on theoretical and analytical frameworks from Critical Discourse Analysis and Systemic Functional Linguistics (Fairclough, 2001; Halliday e Matthiessen, 2004; van Leeuwen, 2008), focusing on the representation of trans social actors within the representation of the social practice of the judicialization of gender identity rights. The data consist of five appellate decisions produced by TJSC between 2007 and 2015. The analysis revealed that all five appellate decisions included misgendering practices at least at the linguistic level, either referring to trans individuals in a way that indicated/revealed their assigned birth name and/or gender in nominal and pronominal choices, or referring to them by using reductionist biological language. The analysis also revealed that the amendment of the official documents of trans social actors depends on their physical characteristics and on clinical reports attesting to a mental condition, thereby reinforcing the idea that their identity derives from a pathological condition.